Family Medicine-Specific Practice-Based Research Network Productivity and Clinical and Translational Sciences Award Program Affiliation. - Haggerty, Treah; Cole, Allison M.; Jun Xiang; Mainous III, Arch G.; Seehusen, Dean; Xiang, Jun; Mainous, Arch G 3rd (Southern Medical Journal, 2017)
Objective: Practice-based research networks (PBRNs) are groups of practices that work together to conduct research. Little is known about the degree to which PBRNs may be achieving success. This is the first general survey of family medicine-based PBRN directors in the United States and Canada to examine research productivity outcomes of PBRNs and explore the association between Clinical and Translational Science Awards (CTSA) program affiliation and PBRN outcomes.Methods: The Council of Academic Family Medicine Educational Research Alliance conducted the survey and e-mailed it to 102 PBRN directors from the Agency for Healthcare Research and Quality's registration.Results: A total of 54 (56%) PBRN directors responded to the survey. PBRNs with an affiliation with a CTSA program were more likely to report completion of quality improvement research and participation in multiple PBRN collaboration research projects. PBRNs affiliated with CTSA programs were less likely to report maintaining funding as a significant barrier.Conclusions: CTSA involvement with PBRNs results in family physician scientists' completing research and disseminating this research through publication. Also, PBRNs with CTSA partnerships have more funding availability. PBRN partnership with a CTSA is beneficial in furthering research in family medicine.